Digital Currency Perception: Preliminary Evidence From Malaysia - Yap, Angeline Kiew Heong; Wong, Siew Chin; Teoh, Melissa Teng Tenk; Saleh, Zakiah (European Publisher, 2019)
Digital currency is an unregulated digital money issued by private developers to general public. The rapid growth and volatility of digital currencies led to an increase of global scrutiny and interest of many stakeholders, issues related to its accountability and security have also been raised. Hence, this paper aims to seek preliminary views on the use of digital currencies, and to examine effectiveness of control measures taken by Bank Negara Malaysia. A questionnaire survey was conducted with 173 responses received from digital currency enthusiasts working in various industries. About 24.3% of the respondents are potential owner; while 10.4% of the respondents are the owners of digital currencies currently. The growth of digital currency investment among Malaysians is also very encouraging. About 29.5% of the respondents are willing to explore digital currency technology and start working on its concrete usage (4%). Furthermore, this paper found that security (54.4%), usability (31.8%) and support and documentation (24.9%) as the main concerns challenging the respondents. In terms of ranking the effectiveness of the control measures taken by Bank Negara Malaysia (2018), “freeze the beneficial owner’s funds or block the transaction” (mean = 3.92) ranked as the most effective measure, followed by “inform the relevant supervisory authorities” (3.88), “ensure the database information is updated/relevant” (3.87) and “submit a suspicious transaction report” (3.79). Findings of this paper contribute to the literature and provides important insights to Bank Negara Malaysia in relation to the enforcement of the relevant requirements and standards for the digital currencies.